Simulation Of Competitiveness Policy For Local Soybean At Domestic Market - Dian Handayani; Tajuddin Bantacut; Jono M. Munandar; Slamet Budijanto (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
Soybean is a strategic commodity which is used as a raw material for food processing and consumed by most of Indonesian people. National demand cannot be covered by local production, due to imported one. This research indicated that soybean harvested area was influenced by local soybean real price, maize real price and last year harvested area. Soybean productivity was influenced by rainfall, maize real price and last year productivity. Local soybean price was influenced by soybean real price at producer level, imported soybean real price, quantity of imported soybean, productivity and last year soybean real price. Soybean real price at producer level was influenced by soybean production, imported soybean quantity, soybean consumption, BULOG monopoly and last year real price at producer level. Soybean import quantity was influenced by production and consumption. Imported soybean price was influenced by international price, exchange rates, import tariff, and last year import price. Combination policy of increase the soybean price and import tariff 20% would stimulate the producer to increase harvested area and production. Strategy to increase competitiveness and national soybean production are through productivity improvement and extended planting area programs. The priority to increase the production is to improve productivity and apply suitable technology. Extension of planting area to better region is conducted to increase cropping index. To anticipate trading liberalization negative effect to farmers’ welfare, protection policy by the government is still needed to control international price fluctuation and to strengthen local soybean competitiveness. Keywords: Strategic commodity, productivity, real price, import quantity, soybean